In utero exposure to polychlorinated biphenyls is associated with decreased fecundability in daughters of Michigan female fisheaters: a cohort study - Han, L.; Hsu, Wei-Wen; Todem, D.; Osuch, J.; Hungerink, A.; Karmaus, W. (My University, 2017)
Background: Multiple studies have suggested a relationship between adult exposures to environmental organochlorines and fecundability. There is a paucity of data, however, regarding fetal exposure to organochlorines via the mother's blood and fecundability of adult female offspring. Methods: Data from a two-generation cohort of maternal fisheaters was investigated to assess female offspring fecundability. Serum concentrations of polychlorinated biphenyls (PCBs) and 1,1-bis-(4-chlorophenyl)-2,2-dichloroethene (DDE) in Michigan female anglers were serially measured between 1973 and 1991 and used to estimate in utero exposure in their female offspring using two different methods. The angler cohort included 391 women of whom 259 provided offspring information. Of 213 daughters aged 20-50, 151 participated (71 %) and provided information for time intervals of unprotected intercourse (TUI). The daughters reported 308 TUIs (repeated observations), of which 288 ended in pregnancy. We estimated the fecundability ratio (FR) for serum-PCB and serum-DDE adjusting for confounders and accounting for repeated measurements. An FR below one indicates a longer time to pregnancy. Results: Compared to serum-PCB of <2.5 mu g/L, the FR was 0.60 for serum-PCB between 2.5-7.4 mu g/L [95 % confidence intervals (CI) 0.36, 0.99], and 0.42 [95 % CI 0.20, 0.88] for serum-PCB > 7.4 mu g/L. Similar results were obtained using the alternative statistical method to estimate in utero serum-PCB. The association was stronger for TUIs when women planned a baby; FR = 0.50 for serum-PCB between 2.5-7.4 mu g/L, [95 % CI 0.29, 0.89], and 0.30 [95 % CI 0.13, 0.68] for serum-PCB > 7.4 mu g/L. There was no relationship between in utero exposure to DDE and fecundability in daughters. Conclusions: Decreased fecundability in female offspring of fisheaters was found to be associated with PCB exposure in utero, possibly related to endocrine disruption in the oocyte and/or other developing organs influencing reproductive capacity in adulthood.
Citation: Han, L., Hsu, W. W., Todem, D., Osuch, J., Hungerink, A., & Karmaus, W. (2016). In utero exposure to polychlorinated biphenyls is associated with decreased fecundability in daughters of Michigan female fisheaters: a cohort study. Environmental Health, 15, 13. doi:10.1186/s12940-016-0175-3
Keywords: Pcb; Dde; Fecundability; Offspring; In Utero; Fisheaters